2012
DOI: 10.5194/acp-12-9013-2012
|View full text |Cite
|
Sign up to set email alerts
|

CO<sub>2</sub>(ν<sub>2</sub>)-O quenching rate coefficient derived from coincidental SABER/TIMED and Fort Collins lidar observations of the mesosphere and lower thermosphere

Abstract: Abstract. Among the processes governing the energy balance in the mesosphere and lower thermosphere (MLT), the quenching of CO 2 (ν 2 ) vibrational levels by collisions with O atoms plays an important role. However, there is a factor of 3-4 discrepancy between the laboratory measurements of the CO 2 -O quenching rate coefficient, k VT , and its value estimated from the atmospheric observations. In this study, we retrieve k VT in the altitude region 85-105 km from the coincident SABER/TIMED and Fort Collins sod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…Remsberg et al (2008) found that the uncertainties associated with the CO 2 VMR contributed one of the largest sources of systematic error in the non-LTE region, with uncertainty values of 1. Feofilov et al, 2012;Panka et al, 2017), and the uncertainties associated with CO 2 (ν 2 ) vibrational quanta exchange rate constant (k vv ). García-Comas et al (2008) demonstrated that the non-LTE region T k (z) errors vary with both latitude and season and were largest during the polar summer (compared to a midlatitude summer location).…”
Section: 1029/2018jd028742mentioning
confidence: 99%
“…Remsberg et al (2008) found that the uncertainties associated with the CO 2 VMR contributed one of the largest sources of systematic error in the non-LTE region, with uncertainty values of 1. Feofilov et al, 2012;Panka et al, 2017), and the uncertainties associated with CO 2 (ν 2 ) vibrational quanta exchange rate constant (k vv ). García-Comas et al (2008) demonstrated that the non-LTE region T k (z) errors vary with both latitude and season and were largest during the polar summer (compared to a midlatitude summer location).…”
Section: 1029/2018jd028742mentioning
confidence: 99%
“…Since only 2.4 % of the N 2 molecules participate in the RV energy transfer process, the rate coefficient for deactivation of CO 2 (v 2 ) by N 2 would be k VT (N 2 ) = ((2.32 ± 1.1) × 0.024) × 10 −12 = (5.6 ± 2.6) × 10 −14 . A larger calculated rate coefficient k N 2 would not be a problem, since the v 2 mode of CO 2 at least up to 90 km altitude is in local thermodynamic equilibrium (LTE); i.e., its vibrational temperature is nearly the same as the translational temperature (Feofilov et al, 2012;Stair et al, 1985). Tables 1a-d, using the atmospheres, provided by Feofilov and López-Puertas, give the rate coefficients k VT (N 2 ), the fifth column, and k VR (N 2 ), the last column, required by k x given by these atmospheres.…”
Section: Thermal Rotational Levelsmentioning
confidence: 99%
“…Later analyses of space-based observations have given values around 6×10 −12 (cm 3 s −1 ) Ratkowski et al, 1994;Gusev et al, 2006;Feofilov et al, 2012, and references therein), except for the Vollmann and Grossmann (1997) study giving a value of 1.5 × 10 −12 (cm 3 s −1 ). The study of Feofilov et al (2012) determined the rate coefficient by coincidental SABER/TIMED and Fort Collins sodium lidar observations in the MLT region and arrived at values of (5.5 ± 1.1) × 10 −12 cm 3 s −1 at 90 km altitude and (7.9 ± 1.2) × 10 −12 cm 3 s −1 at 105 km, with an average value of (k ATM = 6.5 ± 1.5) × 10 −12 cm 3 s −1 . The study of "suggests a value of between 3 and 6 × 10 −12 cm 3 s −1 at 300 K" and temperature "independent or negative temperature dependence".…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations